Africa-RISING early win project - Testing participatory assessment tools for crop-livestock production in Ethiopia - Duncan, Alan J.; Valbuena, Diego (International Livestock Research Institute, 2012)
The Africa RISING program (http://africa-rising.net) comprises three linked research-for-development projects, funded by the USAID Feed the Future Initiative. To produce some short-term outputs and to support the longer term objectives of the projects, in 2012 Africa RISING funded several small, short-term projects in each of the regions. Here Alan Duncan (ILRI) and Diego Valbuena (SLP) introduce two projects that aim to test and adapt participatory approaches and tools for to intensify crop-livestock production at farm and community levels in the Ethiopian Highlands.